Gurez – A native sheep breed of Kashmir - Rather, Mubashir Ali; Hamadani, Ambreen; Ahangar, Showkat Ahmad; Alam, Safeer (Indian Farming, 2021)
It is concluded that sheep farming in Gurez is practiced by marginal farmers of middle age group having marginal land holdings and low income. The Gurez sheep are active and adapted to harsh climate of hilly terrain of the area and the conservation of this breed should be a top priority. It is because this breed is not just an important animal resource, but also a significant contributor to the livelihood of the poor farmers.